Rock magnetic data from Willendorf/Austria - Christian Zeeden; Ulrich Hambach (PANGAEA, 2021)
Here, we report on environmental magnetic analyses including anisotropy of the magnetic susceptibility (AMS) carried out on loessic aeolian sediments at the Willendorf site. Data on lineation, foliation and the degree of anisotropy were used to assess depositional and post-depositional magnetic fabric properties and to deduce site-specific environmental processes. Overall, the loess is of aeolian origin and shows magnetic enhancement and magnetic fabric properties similar to those of other European loess geoarchives. Whilst at face value the AMS properties are indicative of pure aeolian loess consistent with previous studies, imbrication suggests post-depositional slope movement towards the Danube, which obscures inferences on palaeo-wind direction.